CMBD: a manually curated cancer metabolic biomarker knowledge database. (9th March 2021) - Chen, Jing; Liu, Xingyun; Shen, Li; Lin, Yuxin; Shen, Bairong
Abstract: The pathogenesis of cancer is influenced by interactions among genes, proteins, metabolites and other small molecules. Understanding cancer progression at the metabolic level is propitious to the visual decoding of changes in living organisms. To date, a large number of metabolic biomarkers in cancer have been measured and reported, which provide an alternative method for cancer precision diagnosis, treatment and prognosis. To systematically understand the heterogeneity of cancers, we developed the database CMBD to integrate the cancer metabolic biomarkers scattered over literatures in PubMed. At present, CMBD contains 438 manually curated relationships between 282 biomarkers and 76 cancer subtypes of 18 tissues reported in 248 literatures. Users can access the comprehensive metabolic biomarker information about cancers, references, clinical samples and their relationships from our online database. As case studies, pathway analysis was performed on the metabolic biomarkers of breast and prostate cancers, respectively. 'Phenylalanine, tyrosine and tryptophan biosynthesis', 'phenylalanine metabolism' and 'primary bile acid biosynthesis' were identified as playing key roles in breast cancer. 'Glyoxylate and dicarboxylate metabolism', 'citrate cycle (TCA cycle)', and 'alanine, aspartate and glutamate metabolism' have important functions in prostate cancer. These findings provide us with an understanding of the metabolic pathway of cancer initiation and progression. Database URL : http://www.sysbio.org.cn/CMBD/